The Senate and the Civil War 1922-1925 : Prologue, duration and protracted aftermath - Stafford, Mary (Trinity College (Dublin, Ireland). Department of History, 2012)
The Senate of the Irish Free State is the principal focus of this study. The subject is approached from a variety of perspectives within the specific context of the Irish civil war. The time-frame encompasses the civil war years from 1922 to 1925 and the completion of the Senate’s first triennial term. The following interrelated questions are examined: firstly, who were the members of the Upper House and what was the origin and evolution of the Senate as institution, which was inaugurated on 11 December 1922? Allied to this, as Anglo-Irish relations were central to political circumstances; what were the factors, historical and political leading to the Revolution, whose protracted resolution culminated in the civil war? Secondly how and in what manner did members of the Senate contribute to legislation and nation building as founder members of the new state? Thirdly, why did this group, who were in no way involved in the conflict at the onset, conventional or early guerrilla phases of the campaign, on becoming members of the Seanad become the centre and focus of some of the most destructive and virulent excesses of the civil war? Through exploration and analysis the central questions of this study will establish why and how the enduring perception of this body has served to overshadow and obscure the true features and characteristics of the Senate of the Irish Free State.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin